Technology, skills and the pre-modern economy in the East and the West : essays dedicated to the memory of S.R. Epstein - Epstein, Stephan R., 1960-2007; Prak, Maarten Roy, 1955-; Zanden, J. L. van (Global economic history series, 2013)
Technology, Skills and the Pre-Modern Economy investigates, through regional studies and paired comparisons, how technological skills and knowledge were reproduced and disseminated in the advanced agrarian societies of China, India, Russia and Europe in the centuries before the Industrial Revolution.